Applications of AI information technology in psychological education - Jing Huang; Sabariah Sharif; Bee Seok Chua (Journal Of Electrical Systems, 2024)
Information technology and education have recently been integrated into every subject. Here, based on the application of artificial intelligence in information technology and its practice in the communication of psychological education, we look into the application of artificial intelligence in information technology for psychological education. For developing countries, artificial intelligence has a growing role in carrying out comprehensive development in computer instruction to offer superior quality, efficient, and individually focused training that replicates the main characteristics of other computers. The aim is to develop an adaptive, easy-to-operate, and practical computer instruction recovery method with a better curative effect under artificial intelligence technology The use of artificial intelligence has expanded rapidly in recent years. The study aims to provide information technology in education, as students and staff must turn to the international network to complete electronic tasks, such as handling the material. The study's objective is to explore how the AI-based system enhances learning outcomes through reviews of previous literature and direct analyses and assistance with faculty. The outcomes display the current feasibility that further expenditure on additional skills determines superior added value with the assistance of the distributed system. An in-depth discussion of the overall study is included. The rising development in artificial intelligence has strongly promoted the rapid advancement of all sectors, particularly in the field of automated computers.